Vancomycin Revisited – 60 Years Later - Rubinstein, Ethan; Keynan, Yoav (Frontiers in Public Health, 2014)
Vancomycin is one of the older antibiotics that has been now in clinical use close to 60 years. Earlier on, vancomycin was associated with many side effects including vestibular and renal, most likely due to impurities contained in early vancomycin lots. Over the years, the impurities have been removed and the compound has now far less vestibular adverse effects, but still possesses renal toxicity if administered at higher doses rendering trough serum levels of >15 mcg/mL or if administered for prolonged periods of time. Vancomycin is effective against most Gram-positive cocci and bacilli with the exception of rare organisms as well as enterococci that became vancomycin resistant, mostly Enterococcus faecium. The major use of vancomycin today is for infections caused by methicillin-resistant Staphylococcus aureus (MRSA), methicillin-resistant Staphylococcus epidermidis (MRSE) and amoxicillin-resistant enterococci. In its oral form, vancomycin is used to treat diarrhea caused by Clsotridium difficile. With S. aureus, there are only a handful of vancomycin-resistant strains. Nevertheless, a “vancomycin creep” that is slow upward trending of vancomycin MIC from <1 mcg/mL to higher values has been noted in several parts of the world, but not globally, and strains that have MIC’s of 1.5–2 mcg/mL are associated with high therapeutic failure rates. This phenomenon has also been recently recognized in methicillin-susceptible S. aureus (MSSA). While vancomycin is relatively a safe agent adverse events include the “red man” syndrome, allergic reactions, and various bone marrow effects as well as nephrotoxicity. Vancomycin has been a very important tool in our therapeutic armamentarium that remained effective for many years, it is likely remain effective as long as resistance to vancomycin remains controlled.